1990
DOI: 10.1002/hep.1840110418
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine–Induced Liver Cell Injury: Comparison of Morphological Features in Man and in Experimental Models

Abstract: Although investigative research of animal models in cocaine metabolism and associated liver cell injury has been fairly extensive during the past 10 yr, little evidence of hepatotoxicity has been documented in man. We report a case of fulminant hepatic failure and acute rhabdomyolysis resulting from cocaine use. Coagulative-type perivenular and midzonal necrosis and periportal microvesicular fatty change were the predominant morphological features throughout all lobules of the liver, in contrast to periportal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(63 citation statements)
references
References 34 publications
0
60
0
3
Order By: Relevance
“…Suggested pathogenesis is the following: cocaine is metabolized in liver by CYP450, particularly CYP2E1 and CYP2A, to norcocaine, which is metabolized to free radicals causing oxidative stress and lipid peroxidation in hepatocytes. Despite this, it is believed that liver abnormalities in cocaine users could be also related to viral hepatitis from injection drug use, alcoholic liver disease, concurrent rhabdomyolysis, use of other hepatotoxic drugs, or other consequences of a drug-using lifestyle, rather than cocaine by itself [10][11][12]. An observational, 8-year period study in the United States identified 39 patients with acute cocaine intoxication and rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested pathogenesis is the following: cocaine is metabolized in liver by CYP450, particularly CYP2E1 and CYP2A, to norcocaine, which is metabolized to free radicals causing oxidative stress and lipid peroxidation in hepatocytes. Despite this, it is believed that liver abnormalities in cocaine users could be also related to viral hepatitis from injection drug use, alcoholic liver disease, concurrent rhabdomyolysis, use of other hepatotoxic drugs, or other consequences of a drug-using lifestyle, rather than cocaine by itself [10][11][12]. An observational, 8-year period study in the United States identified 39 patients with acute cocaine intoxication and rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…52 An alternative route of metabolism through hydrolysis by esterases in plasma and liver is actually the predominant route of metabolism and generates nontoxic metabolites. 48,49,53,54 Esterase inhibitors potentiate hepatotoxicity by routing more parent drug through P450 pathways. Conversely, induction of esterases (e.g.…”
Section: Drugs Of Abusementioning
confidence: 99%
“…56 However, most of the cases in the literature and in our clinical experience occur in the setting of rhadomyolysis (which itself can increase both aspartate aminotransferase and ALT), disseminated intravascular coagulopathy (DIC), hypotension, hypoxemia, and/or hyperpyrexia and are associated with centrilobular necrosis when histology is available. 53,57,58 A common additional feature has been microvesicular steatosis in the zones spared of necrosis, 57 55 39 consecutive cases of cocaine-associated rhadomyolysis, 23 had liver abnormalities (of which the ALT in 16 was more than 10-fold increased). Hypotension and DIC were seen in 50% of cases with liver abnormalities, and hyperpyrexia was seen in 75%.…”
Section: Drugs Of Abusementioning
confidence: 99%
“…Cocaine-induced liver toxicity has been studied extensively in mice [2,3] and reported in a few clinical cases among humans [4][5][6] . It has been described as a spectrum of disease ranging from minimal elevation of liver enzymes to severe hepatic failure [7] and death.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described as a spectrum of disease ranging from minimal elevation of liver enzymes to severe hepatic failure [7] and death. Severe hepatic injury resulting in marked elevation of liver enzymes and often in association with rhabdomyolysis, has been shown to result in poor outcomes including refractory hypotension, hypoglycemia, seizures, liver failure, disseminated intravascular coagulopathy, acute renal failure and death [4,5,8] . However to our knowledge, severe hepatic injury from cocaine use, with features of shock liver, resulting in spontaneous resolution and minimal to no health consequences has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%